Gold in Ores of the Natalka Giant Deposit (North East Russia): Content, Distribution and Speciation - Kravtsova R.G.; Makshakov A.S.; Tauson V.L.; Lipko S.V.; Belozerova O.Yu. (My University, 2025)
The content, distribution and speciation of gold in ores of the Natalka deposit (North East Russia) were studied. According to atomic absorption spectrometry (AAS), the vein and veinlet-vein ores are highest grade in gold, whereas veinlet-disseminated ores are lower grade and disseminated ores are poor in gold. According to light microscopy and electron probe microanalysis, up to 85% of gold in the Natalka ores is represented by large and small grains of free native gold associated with gangue and sulfide minerals. The gold grains of 0.01 to 2 mm in size are dominated and their fineness vary from 720 to 860 ‰. Up to 20% of native gold is represented by finely dispersed particles < 0.01 mm in size and a fineness of 750–990‰. Most of this gold is fixed and bounded mainly to with sulfides. According to “phase” chemical analysis with AAS, arsenopyrite is richest in gold whereas pyrite is poorer in gold. Using AAS with analytical data selections for single crystals, two non-mineral forms of “invisible” gold were found in these sulfides, namely the structurally bound (structural) and surficially bound (surficial) forms. The structural gold is incorporated into the mineral structure. The surficial form is confined to nano-sized non-autonomous phases on the sulfide mineral surfaces and often dominates over the structural form. The maximum gold concentrations on the surface of arsenopyrite and pyrite were confirmed by LA-ICP-MS data. It is expected that not all “invisible” gold is a refractory gold. The major part of gold contained in arsenopyrite and pyrite as finely dispersed, micron- and submicron-sized particles, as well as the surficially bound gold, can be extracted with modification of current flowsheet, which enhances the value of the gold ores at the Natalka deposit.
Keywords: Natalka deposit; gold; ores; content; distribution; gangue minerals; sulfide minerals; arsenopyrite; pyrite; speciation